Information rules a strategic guide to the network economy - Shapiro, Carl 1955-; Varian, Hal R. 1947- (Harvard Business School, 1998)
In Information Rules, authors Shapiro and Varian reveal that many classic economic concepts can provide the insight and understanding necessary to succeed in the information age. They argue that if managers seriously want to develop effective strategies for competing in the new economy, they must understand the fundamental economics of information technology. Whether information takes the form of software code or recorded music, is published in a book or magazine, or even posted on a website, managers must know how to evaluate the consequences of pricing, protecting, and planning new versions of information products, services, and systems. The first book to distill the economics of information and networks into practical business strategies, Information Rules is a guide to the winning moves that can help business leaders navigate successfully through the tough decisions of the information economy. Subjects covered include: Competitive advantage, Economic analysis, Game theory, Information age, Information economy, Information technology, Intellectual property, Marketing strategy, New economy, Pricing, Pricing strategy, Value of information
Keywords: Informatietechnologie; Société informatisée; Strategisch management; Technologie de l'information - Aspect économique; Information society; Information technology -- Economic aspects; Wettbewerbsstrategie; Wirtschaft; Informationswirtschaft; Informationsökonomie; Unternehmen; Informationstechnik; Electronic Commerce; Internet